Application of Single Exponential Smoothing and Double Exponential Smoothing in Forecasting Sales at Zoey Mart Stores - Rochim, Bahrur; Yuana, Haris; Febrinita, Filda (CV. Rayyan Dwi Bharata, 2025)
This research evaluates the Single Exponential Smoothing (SES) and Double Exponential Smoothing (DES) methods to predict sales of Fortune pillow oil at the Zoey Mart Store, which experiences sales fluctuations. SES with an alpha value of 0.5 produces a forecast of 285 items for January 2024, while DES with an alpha of 0.5 and beta 0.7 produces 338 items. Forecasting accuracy is measured using Mean Absolute Deviation (MAD) and Mean Absolute Percentage Error (MAPE). The results show that SES has a MAD of 73.82 and a MAPE of 28.81%, while DES has a MAD of 44.66 and a MAPE of 18.80%, but with lower responsiveness to changes in sales patterns. DES has lower accuracy and responsiveness , therefore this research recommends the use of DES for fluctuating sales at Zoey Mart, because DES is more suitable for these conditions. This guide helps Zoey Mart in better planning stock and estimating operational costs, especially in the face of uncertainty due to sales fluctuations.